Kontribusi.Kepemimpinan Kepala Sekolah, Lingkungan Kerja Terhadap Kepuasan Kerja Guru Smp Kecamatan Sindang Beliti Ilir Kabupaten Rejang Lebong - Sampurnah; Somantri , Manap; sumarsih (UNIVERSITAS BENGKULU, 2024)
The purpose of this research is to analyze the contribution of the principal's leadership and work environment to the job satisfaction of state junior high school teachers in Sindang Beliti Ilir District, Rejang Lebong Regency. This research method uses a quantitative approach with the type of correlation. The research population was 44 teachers using a total sample. Collecting data using questionnaires and data analysis using hypothesis testing with multiple regression formulas. The results showed that there was a positive contribution of the principal's leadership, and the work environment together on teacher job satisfaction of 0.21%. That is, the principal's leadership and a good work environment together increase the job satisfaction of junior high school teachers, Padang Ulak Tanding District, Rejang Lebong Regency